ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP NILAI PERUSAHAAN MELALUI KEBIJAKAN DIVIDEN (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014-2016) - Maharesi Sekarlangit Maretiningrum H.R, 14.05.52.0211; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2018)
This study aims to examine and analyze the effects of profitability, institutional ownership, and firm size of firm value with dividend policy as intervening variable on Manufacturing Companies Listed on IDX Period 2014-2016. The population in this study is all Manufacturing Companies Registered in IDX Period 2014-2016. The sample selection using purposive sampling method and obtained 206 companies.The results of the research show that profitability, institutional ownership, firm size, and dividend policy influence has positive significant of firm value. Dividend policy has a mediating effect between profitability to firm value, but dividend policy has no mediating effect between institutional ownership and firm size to firm value .Keywords: Firm value, Profitability, Institutional Ownership, Firm Size, Dividend Policy